Makna Budaya Lagu Daerah Tontemboan - Rawung, Christina (Universitas Sam Ratulangi, 2015)
Kapoya village is located in SouthMinahasa precisely in the District Suluun-Tareran. Problems of this research,what is the folk songs in Tontemboan areas that exist in Kapoya village andwhat is the function, what cultural meanings contained in the Tontemboan folksongs, and why villagers of Kapoya still sing the Tontemboan folk songs basedon their reflected the mindset. The purpose of this study is to identify the Tontemboanfolk songs and explain its function, explains the cultural meaning of theTontemboan folk songs, and explain the reason for the villagers of Kapoya stillsing the Tontemboan folk songs based on their reflected the mindset.This study used descriptive method withqualitative approach. The observation point chosen five informants. The firstone as the main informant and the other as a companion. In this study,collected twenty-seven folk songs in Tontemboan.In terms of meaningful culturalTontemboan folk songs in the Kapoya village and their functions, which consistsof 27 traditional songs and their functions. In terms of cultural meaningscontained in Tontemboan folk songs have some deep meaning, such as the peopleof Kapoya village who believe in the power of God as the Creator, the publicbelieves that happen compassion into the new year is a joy to remember therelatives and siblings. In terms of folk songs sung reason thatis the mindset of the villagers of Kapoya, namely as guidelines, instructions,and the correct way for a person to live a life based onwhat he believes and meaningful bring compassion, happy, respectful, and proudof the life lived in the Kapoya village.Keywords: Culture, Tontemboan, Kapoya